The state of cancer research in fragile and conflict-affected settings in the Middle East and North Africa Region: A bibliometric analysis - Sater, Zahi Abdul; Farhat, Theresa; Elsayed, Mohamed N.; Youssef, Yara; Husain, Marium; Kaddoura, Malak; Jaber, Lubna; Mukherji, Deborah; Taher, Ali (Frontiers in Oncology, 2023)
Background: Cancer represents a disproportionate burden in LMICs, especially conflict-affected countries in the MENA region. Research output on cancer fails to match the growing burden in the region. This bibliometric study aims to examine the status and trends of cancer research in fragile and conflict-affected settings in the MENA region from 2000 to 2021, while also incorporating economic and demographic indicators as additional factors of analysis. Methods: The Web of Science databases were searched for publications related to cancer research in Iraq, Lebanon, Libya, Palestine, Syria, and Yemen from January 1, 2000, to December 31, 2021. The retrieved publications were screened based on preset eligibility criteria and the final list was analyzed using the Bibliometrix Package in R to generate the annual scientific production and citations, journals, institutions, authors, collaborations, keywords, and title co-occurrence. Each country’s annual scientific production was analyzed against its annual GDP per capita. Results: A total of 4,280 documents met the inclusion criteria in this research. The annual number of publications revealed a significant increase over the past 20 years. These publications were mostly published in international journals that had impact factors rated in the 3rd or 4th quartiles. The overall contribution of researchers from Fragile and Conflict-Affected Settings (FCS) to cancer research was 6.5% of the MENA cancer research productivity, despite comprising around 23% of the total MENA region’s population. Lebanon had the highest publication productivity at the country level, followed by Iraq and Syria. GDP per capita was not significantly correlated with cancer research across the countries under investigation. At the institutional level, the American University of Beirut was the most prolific institution and had the highest number of collaborations and the widest range of cooperative partners. Most first authors were male researchers. There is an interest in cancer expression, prevalence, diagnosis, and management in terms of commonly researched topics. Conclusion: This study underscores the need for a concerted effort to improve cancer research outcomes in FCS, which can be achieved through targeted research, increased investment in research infrastructure and capacity-building initiatives, and greater regional and global collaboration.